2014
DOI: 10.1021/jp5002918
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Mechanism of the Covalent Coupling Between Terminal Alkynes on a Noble Metal

Abstract: The mechanism of the newly reported route for surface-assisted covalent coupling of terminal alkynes on Ag(111) is unraveled by density functional theory based transition state calculations. We illustrate that the reaction path is fundamentally different from the classical coupling schemes in wet chemistry. It is initiated by the covalent coupling between two molecules instead of single-molecule dehydrogenation. The silver substrate is found to play an important role stabilizing the intermediate species by che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
92
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 57 publications
9
92
0
Order By: Relevance
“…Glaser-Hay coupling, a wellknown named reaction, proceeds identically through the dehydrogenation of a terminal alkyne with a Cu(I) ion and establishment of a Cu-acetylide intermediate. The mechanism for the surface-assisted covalent coupling of terminal alkynes on Ag (111) was elucidated using density functional theory (DFT)-based transition state calculations, 18 suggesting a hierarchic reaction pathway that is fundamentally different from the classical coupling schemes in wet chemistry. However, research findings on Ag-related syntheses of butadiyne moieties remain scarce.…”
Section: Alkynylationmentioning
confidence: 99%
“…Glaser-Hay coupling, a wellknown named reaction, proceeds identically through the dehydrogenation of a terminal alkyne with a Cu(I) ion and establishment of a Cu-acetylide intermediate. The mechanism for the surface-assisted covalent coupling of terminal alkynes on Ag (111) was elucidated using density functional theory (DFT)-based transition state calculations, 18 suggesting a hierarchic reaction pathway that is fundamentally different from the classical coupling schemes in wet chemistry. However, research findings on Ag-related syntheses of butadiyne moieties remain scarce.…”
Section: Alkynylationmentioning
confidence: 99%
“…It has been demonstrated that thermal activation can trigger both reactions on various flat metal surfaces (i.e., Au, Ag, Cu), whereby a preference for cyclotrimerization and homocoupling is expressed on Au(111) and Ag(111), respectively. As a drawback, their complex, multistep pathways render these reactions prone to a variety of side‐reactions, thus achieving selective alkyne coupling remains challenging.…”
Section: Figurementioning
confidence: 99%
“…Thus, the explanation of the observed temperature dependence of the prevailing reactions requires a more complex scenario. For its discussion (Figure e), we simplify the proposed pathway for homocoupling to two major steps: 1) Two pristine molecules couple to an intermediate (INT), which is bound to the substrate and has two hydrogen atoms pointing away from the substrate; 2) The INT finalizes the homocoupling by two subsequent dehydrogenation steps. Previous results indicate that cyclotrimerization also proceeds via a two‐step reaction with essentially the same INT .…”
Section: Figurementioning
confidence: 99%
“…In this context, the homocoupling reaction of terminal alkyne tectons has raised great hopes for the construction of graphdiyne‐related nanostructures . However, the intricate coupling mechanism and the occurrence of cross‐linking side reactions prevented so far the production of high‐quality 2D architectures. With the help of substrate templating mechanisms, which proved efficient for increasing regio‐ and chemoselectivity, so‐called extended graphdiyne (GDY) nanowires were realized on a vicinal surface .…”
mentioning
confidence: 99%